Enhancing immunity against carcinogens through probiotics: A literature review - Massoud Attarianshandiz (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2023)
This literature review explores various aspects of using probiotics as a dietary practice to mitigate the effects of toxic compounds. The discussion highlights the importance of considering factors such as timing and composition of probiotic consumption for maximum benefits. Studies have demonstrated the potential of probiotics to inhibit Deoxyribonucleic Acid (DNA) damage and reduce the occurrence of aberrant crypts in animal models when administered before exposure to toxicants. Furthermore, probiotics have been found to metabolize genotoxic compounds into inactive forms, indicating their potential role in detoxification processes. The binding activity of probiotics against toxicants has been widely studied, but there is a need for further research on the metabolites produced during these interactions. Additionally, the presence of other compounds in the food matrix and their competitive effects on probiotic binding should be investigated to understand the full picture. The strain-dependent nature of the probiotic activity and the variability of their antimutagenic properties for different mutagens further highlight the complexity of their functionality. Considering these findings, it is recommended to conduct a careful risk assessment to evaluate the safety of probiotics and their metabolites, taking into account the potential risks and benefits associated with their use. This will help ensure the responsible application of probiotics in food safety and human health initiatives.